Mystic Border. When borders are hidden by the state. Photo Operations on the Thai - Myanmar Border - Jomyim, Ugrid (DEC Journal : Art and Design, 2024)
This paper presents the Dara-Ang ethnic group residing in Ban Nolae, Fang District, Chiang Mai Province, Thailand. The study, which focuses on the community's experiences in the borderland context between Thailand and Myanmar, uses documentary photography and social science concepts to explore the notions of state, border, identity, and power. The fieldwork observations and photographic documentation reveal that the Dara-Ang people struggle with their identity under the influence of capitalism. They are recognized and marginalized by the state, and their existence is fluid and dependent on external forces. This realization transformed documentary photographs into fine art photography through darkroom manipulation. The resulting artworks create new meanings from the film traces, challenging the positioning of borderland ethnic groups as citizens by the state and capitalist systems and questioning their agency within this liminal space.